(-2)^3=\mathbf{(-1)^3}\cdot 2^3=\mathbf{(-1)}\cdot 2^3=(-1)\cdot 8=-8

Resumiendo: (-2)^3=(-)^3\cdot 2^3=-8; (-)^3=-

En general \mathbf{(-)^{Impar}}=-

(-2)^4=\mathbf{(-1)^4}\cdot 2^4=\mathbf{(+1)}\cdot 2^4=16

Resumiendo: (-2)^4=(-)^4\cdot 2^4=16; (-)^4=+

En general \mathbf{(-)^{Par}}=+

Debes distinguir entre (-2)˛ y -2˛, en el primer caso el - está elevado al cuadrado, en el segundo no, así:

\mathbf{(-2)^4=16}   y   \mathbf{-2^4=-16}

(-2)^6

 

 

(-3)^4

 

 

-0.2^6

 

 

(-0.1)^5

 

 

-0.1^0

 

 

(-0.3)^2

 

 

(-0.2)^1

 

 

-0.2^2

 

 

(-10)^0

 

 

-5^5

 

 

0.3^3

 

 

-0.5^2

 

 

-10^1

 

 

-3^2

 

 

(-5)^0

 

 

-0.5^6

 

 

-2^4

 

 

-0.1^6

 

 

-10^1

 

 

(-0.5)^4

 

 

-10^0

 

 

-2^1

 

 

(-4)^4

 

 

0.3^5

 

 

0.2^4

 

 

5^1

 

 

-3^4

 

 

(-0.2)^5

 

 

(-2)^3

 

 

-10^3

 

 

-10^5

 

 

(-2)^1

 

 

(-0.3)^1

 

 

-0.1^2

 

 

-0.2^5

 

 

4^3

 

 

(-2)^4

 

 

-0.4^6

 

 

4^6

 

 

(-2)^4